Analysis of Seblak Consumption and Dysmenorrhea among University Students with Residential Status as an Effect Modifier - Puji Amalliyah; Faradina Aghadiati; Rini Mutahar (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Dysmenorrhea was a common menstrual disorder among female university students that could interfere with academic activities. Irritative dietary patterns, such as consuming seblak—high in capsaicin and sodium—were suspected as triggers for menstrual pain. Objective: This study aimed to analyze the association between seblak consumption and dysmenorrhea, considering residential status as an effect modifier. Methodology: A cross-sectional study was conducted involving 207 female students at Universitas Sriwijaya via quota-convenience sampling. Data were collected using a Food Frequency Questionnaire (FFQ) and a structured questionnaire for functional dysmenorrhea. Data analysis involved logistic regression and stratified analysis using STATA 14. Results: Results show that the prevalence of dysmenorrhea is 39.6%. No significant association exists between seblak consumption and dysmenorrhea in the total sample. However, stratified analysis reveals a significant association among students living with parents (OR=2.76; 95% CI: 1.18–6.42; p=0.019), while no significance is found in boarding houses (p=0.570). Interaction testing confirms residential status as a significant effect modifier (p-interaction=0.020). Conclusion: Seblak consumption significantly increases dysmenorrhea risk among students residing with families, but the influence is distorted by environmental factors in boarding houses. Reproductive health education should consider spicy diet patterns, particularly for groups with high dietary stability at home.